The fang of Bonfire Crossing - McLelland, Brad; Sylvester, Louis (McLelland, Brad. Legends of the lost causes (Series), 2020)
In an 1850s Wild West filled with supernatural beasts and magic-wielding outlaws, Keech and his band of fellow orphans, seeking revenge for their killed families, search for Bonfire Crossing, the Osage land that holds clues to the whereabouts of the all-powerful Char Stone.